Alternativas para intensificar a produção de bovinos de corte em sistema de integração lavoura-pecuária - Scheeren, Fernanda Bernardi (2022)
The objective of this work was to evaluate different finishing systems for beef cattle in a CropLivestock Integration area. Thus, the inclusion of legume and supplementation under winter pasture of black oat (Avena strigosa Schreb) and ryegrass (Lolium multiflorum L.) were evaluated. The proposed treatments were: control (black oat + ryegrass), legume (black oat + ryegrass + legume) and supplementation (black oat + ryegrass + 1% of supplement live weight). This work was carried out for 3 years (2017, 2018 and 2020), using 54 steers (18 animals per year), with an average initial age of 25 ± 3 months, average initial weight of 413.08 ± 4.56 kg of live weight, divided randomly in nine paddocks of 0.7 hectares where the treatments were applied. During the period of evaluation of the animals, they were weighed in intervals of 21 days to adjust the supply of the supplement, with the same interval the pasture was evaluated in relation to the production and its composition was characterized, and to evaluate the nutritional quality of the pasture, the grazing simulation was performed. After the end of the experimental period, determined by the carrying capacity of the pasture, the animals were slaughtered to evaluate the carcasses and meat. The experimental design used was completely randomized (DIC) with three replications (pads with two animals each) for the variables related to pasture and animal performance, and six replications (animal) for the variables corresponding to carcass and meat quality, during the three years of experiment. With supplementation, it was possible to increase productivity per area (97 kg.ha1), as well as animal performance (0.360 kg) and hot carcass weight (27.6 kg). With the inclusion of the legume, it was possible to achieve similar results in the ADG.ha1 and in the slaughter weight of the animals (20.3 kg) that received the supplementation. The live weight gain per hectare per day did not differ between the treatments applied. In this sense, supplementation, as well as leguminous inclusion, may be alternatives for finishing beef cattle in an integrated croplivestock system. In addition, carcass and meat characteristics were not affected by different diets. Thus, the alternative may vary according to the purpose of the system and the cost of supplementation.